Pelatihan Analisis Rasch untuk MGMP Ilmu Pengetahuan Alam SMP/MTs Kabupaten Sumenep - Anekawati, Anik; Matlubah, Helliyatul; Habibi, Habibi (Penerbit Goodwood, 2024)
Purpose: The community service aims to enhance Natural Science teachers’ knowledge related to learning assessment and their skills in processing data using Rasch analysis. Methodology/approach: The community service runs as hybrid training (offline and online) for a teacher community called a Natural Science MGMP, which included 34 Junior High School Natural Science Teachers in the Sumenep Regency. This activity was carried out as training and mentoring for two days, where participants learned Rasch analysis based on theory and practice. They were then required to fill in the pretest and post-test to obtain data regarding participants’ knowledge and skills related to this training. Results: The results of the pre-test and post-test were analyzed using the paired t-test for the knowledge aspect. There was a significant increase after being given Rasch analysis material, since the standard deviation of the post-test was higher than that of the pre-test. On the other hand, the skill aspect also showed a significant increase after Rasch analysis, with a higher standard deviation after treatment. Furthermore, the N-Gain Score was used to determine the extent to which participants’ knowledge and skills differed after training in the Rasch analysis. Limitations: This community service has several limitations including technical problems and participants. Some participants found it difficult to install and operate Ministep/Winstep because such software is not compatible with their device or new software. Moreover, several teachers did not fill in the pre-test and post-test; hence, it was difficult to assess their progress after the training. Contribution: This program can contribute to improving Natural Science teachers’ knowledge and skills in learning assessment, especially for teachers in Sumenep Regency.